1999
DOI: 10.21836/pem19990504
|View full text |Cite
|
Sign up to set email alerts
|

Castration of the stallion: Preferably in the standing horse by laparoscopic techniques?

Abstract: SummaryProgress in the laparoscopic techniques has made it possible to remove an abdominal testicle in the standing horse. As abdominal cryptorchidism is usually unilateral, the descended testicle is removed using a classic standing castration technique. However, this latter technique is not considered ideal as it is difiicult to guarantee asepsis, and can be dangerous for the surgeon. Therefore, a study was initiated to castrate descended testicles in the standing horss using a laparoscopic technique. In six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 3 publications
2
28
0
2
Order By: Relevance
“…The pony was suspected of right sided abdominal cryptorchidism. Standing laparoscopy was recommended to confirm an abdominal location of the testicle and, after localisation, subsequent ligation of the spermatic cord according to previously described techniques (Rijkenhuizen and Grinwis 1999; Rijkenhuizen and Van Dijk 2002). After completion of the laparoscopic procedure, it was planned to castrate the normally descended left testicle using the closed technique by inguinal approach under general anaesthesia (Schumacher 2006).…”
Section: Case Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pony was suspected of right sided abdominal cryptorchidism. Standing laparoscopy was recommended to confirm an abdominal location of the testicle and, after localisation, subsequent ligation of the spermatic cord according to previously described techniques (Rijkenhuizen and Grinwis 1999; Rijkenhuizen and Van Dijk 2002). After completion of the laparoscopic procedure, it was planned to castrate the normally descended left testicle using the closed technique by inguinal approach under general anaesthesia (Schumacher 2006).…”
Section: Case Detailsmentioning
confidence: 99%
“…The (10 mm) portal for the laparoscope 5 was made midway between the last rib and tuber coxae just dorsal to the dorsal boundary of the internal abdominal oblique muscle. Abdominal insufflation was performed routinely (Rijkenhuizen and Grinwis 1999; Rijkenhuizen and Van Dijk 2002). A 5 mm instrument portal was created 5 cm ventral to the laparoscope portal.…”
Section: Case Detailsmentioning
confidence: 99%
“…und Vv. testicularis et ductus deferentis mit anschließender Durchtrennung des Gefäß-Samenstranges distal der Ligaturstelle, so dass der jeweilige Hoden einer aseptischen Nekrose unterliegt (Wilson und Hendrickson 1996, Rijkenhuizen 1999, Rijkenhuizen und van Dijk 2002. Hierbei muss jedoch berücksichtigt werden, dass es bei dieser Kastrationsmethode als postoperative Komplikation zu einer Revaskularisierung noch vitalen Hodengewebes kommen kann (Bergeron et al 1998, Litzke et al 2000 (Abb.…”
Section: Diskussionunclassified
“…Earlier studies performed in donkeys, ponies and horses with normally descended testes have shown that intra‐abdominal ligation of the spermatic cord resulted in avascular necrosis of the testes and a decrease in basal testosterone (Wilson et al . ; Rijkenhuizen and Grinwis ; Walmsley ; Pepe et al . ).…”
Section: Introductionmentioning
confidence: 99%